Adipose tissue‐derived stromal cells are sources of cancer‐associated fibroblasts and enhance tumor progression by dense collagen matrix. Issue 6 (10th October 2018) - Okumura, Takashi; Ohuchida, Kenoki; Kibe, Shin; Iwamoto, Chika; Ando, Yohei; Takesue, Shin; Nakayama, Hiromichi; Abe, Toshiya; Endo, Sho; Koikawa, Kazuhiro; Sada, Masafumi; Horioka, Kohei; et al.
Abstract : Although recent studies revealed that adipose tissue accelerates pancreatic tumor progression with excessive extracellular matrix, key players for desmoplasia in the adipose microenvironment remains unknown. Here, we investigated the roles of adipose tissue‐derived stromal cells (ASCs) in desmoplastic lesions and tumor progression by in vitro and in vivo experiments. In a three‐dimensional (3‐D) organotypic fat invasion model using visceral fat from CAG‐EGFP mice, GFP‐positive fibroblastic cells infiltrated toward cancer cells. When tumor cells were inoculated into transplanted visceral fat pads in vivo, tumor weights and stromal components were enhanced compared to subcutaneous and orthotopic tumor cells inoculated without fat pads. Expression of αSMA in established human ASCs was lower compared to cancer associated fibroblasts, and the 3‐D collagen matrices produced by ASCs cultured in cancer cell‐conditioned medium changed from loose to dense structures that affected the motility of cancer cells. Microarray analyses revealed upregulation of S100A4 in ASCs, while S100A4‐positive stromal cells were observed at extrapancreatic invasion sites of human pancreatic cancer. The present findings indicate that ASCs are recruited to extrapancreatic invasion sites and produce dense collagen matrices that lead to enhanced tumor progression. Both inhibition of ASCs recruitment and activation could lead to a novel antistromal therapy. Abstract : What's new? One of the major pathological features of pancreatic ductal adenocarcinoma is excessive stromal involvement, and anti‐stromal therapies are considered promising against this deadly cancer. Here the authors show in a 3D organotypic fat invasion model or in mice specific infiltration of adipose tissue‐derived stromal cells towards cancer cells and dense collagen production leading to enhanced tumor progression in vivo. They speculate that adipose‐derived stromal cells may be new targets in therapy approaches against pancreatic cancer.